Răspuns :
a = 3²⁰¹³ / 5 - 2 · 3²⁰¹² / 5 - 2· 3²⁰¹¹ / 5 - ....... - 2· 3 / 5
b = - 2 · 3²⁰¹² / 5 - 2· 3²⁰¹¹ / 5 - ....... - 2· 3 / 5 =
= - 2 /5 · ( 3²⁰¹²+ 3²⁰¹¹ + ... + 3¹ )
c = 3²⁰¹²+ 3²⁰¹¹ + ... + 3¹ I · 3
3· c = 3²⁰¹³ + 3²⁰¹² + 3²⁰¹¹ + .........+ 3² scadem
c = 3²⁰¹²+ 3²⁰¹¹ + ........ + 3² + 3¹
---------------------------------------------------------
3 · c - c = 3²⁰¹³ - 3
2· c = 3²⁰¹³ - 3 ⇒ c = 3²⁰¹³ /2 - 3/2
b = - 2/5 · ( 3²⁰¹³ / 2 - 3 /2 ) = - 3²⁰¹³ / 5 + 3 / 5
a = 3²⁰¹³ / 5 - 3²⁰¹³ / 5 + 3/5 = 3 / 5
b = - 2 · 3²⁰¹² / 5 - 2· 3²⁰¹¹ / 5 - ....... - 2· 3 / 5 =
= - 2 /5 · ( 3²⁰¹²+ 3²⁰¹¹ + ... + 3¹ )
c = 3²⁰¹²+ 3²⁰¹¹ + ... + 3¹ I · 3
3· c = 3²⁰¹³ + 3²⁰¹² + 3²⁰¹¹ + .........+ 3² scadem
c = 3²⁰¹²+ 3²⁰¹¹ + ........ + 3² + 3¹
---------------------------------------------------------
3 · c - c = 3²⁰¹³ - 3
2· c = 3²⁰¹³ - 3 ⇒ c = 3²⁰¹³ /2 - 3/2
b = - 2/5 · ( 3²⁰¹³ / 2 - 3 /2 ) = - 3²⁰¹³ / 5 + 3 / 5
a = 3²⁰¹³ / 5 - 3²⁰¹³ / 5 + 3/5 = 3 / 5